Microeconometrics - Durlauf, Steven N.; Blume, Lawrence (New York : Palgrave Macmillan, 2010)
"Following the recent publication of the award winning and much acclaimed The New Palgrave Dictionary of Economics, second edition which brings together Nobel Prize winners and the brightest young scholars to survey the discipline, we are pleased to announce The New Palgrave Economics Collection. Due to demand from the economics community these books address key subject areas within the field. Each title is comprised of specially selected articles from the Dictionary and covers a fundamental theme within the discipline. All of the articles have been specifically chosen by the editors of the Dictionary, Steven N. Durlauf and Lawrence E. Blume and are written by leading practitioners in the field. The Collections provide the reader with easy to access information on complex and important subject areas, and allow individual scholars and students to have their own personal reference copy"--Provided by publisher.
Categorical data / A. Colin Cameron -- Competing risks model / Gerard J. Van Den Berg -- Computational methods in econometrics / Vassilis A. Hajivassiliou -- Control functions / Salvador Navarro -- Decision theory in econometrics / Keisuke Hirano -- Difference-in-difference estimators / Alberto Abadie -- Exchangeability / David Draper -- Extreme bounds analysis / Edward E. Leamer -- Field experiments / John A. List and David Reiley -- Fixed effects and random effects / Badi H. Baltagi -- Identification / Jean-Marie Dufour and Cheng Hsiao -- Local regression models / Oliver B. Linton -- Logit models of individual choice / Thierry Magnac -- Longitudinal data analysis / Chang Hsiao -- Matching estimators / Petra E. Todd -- Maximum score methods / Robert P. Sherman -- Mixture models / Bruce G. Lindsay and Michael Stewart -- Natural experiments and quasi-natural experiments / J. Dinardo -- Nonlinear panel data models / Ekaterini Kyriazidou -- Nonparametric structural models / Rosa L. Matzklin -- Partial identification in econometrics / Charles F. Manski -- Partial linear model / Elie Tamer -- Propensity score / Jinyoung Hahn -- Proportional hazard model / Jerry A. Hausman and Tieman M. Woutersen -- Quantile regression / Moshe Buchinsky -- Regression-discontinuity analysis / Wilbert VanDerKlaauw -- Roy model / James J. Heckman and Christopher Taber -- Rubin causal model / Guido W. Imbens and Donald B. Rubin -- Selection bias and self-selection / James J. Heckman -- Semiparametric estimation / James L. Powell -- Simulation-based estimation / Eric Renault -- Social interactions (empirics) / Yannis M. Joannides -- Spatial econometrics / Timothy G. Conley -- Survey data, analysis of / Jeff Dominitz and Arthur Van Soest -- Tobit model / Jean-Marc Robin -- Treatment effect / Joshua D. Angrist -- Variance, analysis of / Andrew Gelman.
All articles first published in The new Palgrave dictionary of economics, 2nd ed. in eight volumes, 2008 exception of Selection bias and self-selection which first published in The new Palgrave: a dictionary of economics, in four volumes, 1987.
Includes bibliographical references and index.
Keywords: Microeconomics -- Econometric models